2008
DOI: 10.1021/cm8023007
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical, Magnetic, and Electrical Properties of α,ω-Capped Sexithiophene Films. Part 3. Conduction in Poly(bis-terthienyl-B)s (B = Ethane, Disulfide, Diacetylene, Acetylene, Ethylene)

Abstract: Electrochemical oxidation of bis-terthienyl-B (B = ethane, disulfide, diacetylene, acetylene, ethylene) has been investigated. Monomers without and with 3,3′′-dialkylsubstitution are regularly coupled to polymers alternating sexithiophene and B moieties. The corresponding terthienyl homopolymers have also been produced for comparison. The polymers obtained are characterized by cyclic voltammetry, EQCM, UV−vis, and FTIR spectroscopy, in situ ESR and in situ conductivity. The conductivities of p-doped polymers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Nowadays, the two bands electrode has been replaced by more sophisticated electrodes arrangements. The main limitation of this type of parallel microelectrodes, is that conductivity values smaller than 0.1 Ω −1 cm −1 cannot be obtained . This first system was improved by Harima et al ., who used as working electrode a four‐band platinum electrode for in‐situ conductivity measurement of PANI (Figure b) .…”
Section: Equipment and Technical Fundamentals Of The In Situ Electrocmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the two bands electrode has been replaced by more sophisticated electrodes arrangements. The main limitation of this type of parallel microelectrodes, is that conductivity values smaller than 0.1 Ω −1 cm −1 cannot be obtained . This first system was improved by Harima et al ., who used as working electrode a four‐band platinum electrode for in‐situ conductivity measurement of PANI (Figure b) .…”
Section: Equipment and Technical Fundamentals Of The In Situ Electrocmentioning
confidence: 99%
“…The main limitation of this type of parallel microelectrodes, is that conductivity values smaller than 0.1 Ω À 1 cm À 1 cannot be obtained. [45][46][47] This first system was improved by Harima et al, who used as working electrode a four-band platinum electrode for in-situ conductivity measurement of PANI ( Figure 3b). [48] An additional power supply (3) ( Figure 3b) is needed to apply the V d between the inner electrodes.…”
Section: Systems Using Band Electrodesmentioning
confidence: 99%
“…Poly(disulfide) 67 was prepared as part of a series of polymers with alternating sexithiophene sequences and bridge moieties of varied conjugation. 44 The disulfide was of interest because of a possible participation of the electron-rich S-S moiety to the conjugated path. However, the conductivities of p-doped 67 suggested that conduction proceeds via a direct hopping between stacked sexithiophene moieties of cofacial polymer chains.…”
Section: Photosystemsmentioning
confidence: 99%
“…[ 18 ] Formation of the disulfi de bond is an effective way to extend the length of oligothiophenes. [19][20][21] Compared to oligothiophene polymers, disulfi de oligothiophene polymers have worse π -conjugated systems and lower conductance. Nevertheless, the conductivity of polymers can be signifi cantly increased when a dopant is used.…”
Section: Doi: 101002/adma200904026mentioning
confidence: 99%